Cross Border SMEs: Malaysia & Indonesia - Hendar, H (UNISSULA, 2022)
SMEs have a very important role in the country's economy, In 2019, Bank Indonesia estimates that the contribution of SMEs to GDP will reach 64 percent, 14 percent for exports and 95 percent for employment. In Malaysia, the contribution of SMEs to GDP reached 38.3% . In 2018 from 6.2 % in 2017. This segment plays an important role in Malaysia's growth as it accounts for 98.5% of total registered businesses. This proves that SMEs have a strategic role as a means of alleviating poverty and equalizing the welfare of the middle-class community. Even so, if SMEs become a priority sector that needs to be continuously encouraged to increase national economic growth. However, the reality of SMEs is currently is currently still full of obstacles, especially those related to limited market access, competitiveness, inadequate use technology, management and limited access to finance. Besides, digitalization of business and on line marketing as well as increasing exports can be a way for SMEs to survive in as environment of global competition. This is a challenge for SMEs in facing various economic crises.